1969
DOI: 10.1079/bjn19690040
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate utilization in the pre-ruminant calf

Abstract: I . Changes in blood sugar levels after giving carbohydrates have been used to assess carbo-2. Glucose, galactose and lactose were readily utilized by all calves; the utilization of glucose 3. Maltose and fructose utilization was low in young calves and increased slightly with age. 4. Sucrose and starch were not utilized. 5. Studies with three older pre-ruminant calves (aged 53, 88 and 106 days) in which the carbohydrates were infused into the proximal duodenum showed that glucose, galactose, lactose and xylos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…2A and B, 3A and B). Ulbrich studying human newborns each demonstrated large increases in peripheral glucose concentration and much smaller changes in peripheral galactose concentration after lactose ingestion, similar to the arterial data we report in Figures 2A and 3A. Siddons et al (14) gave lactose to preruminant calves and found quantitatively large increases in peripheral and Glupv with much smaller increases in the peripheral and Galpv. However, Siddons et al (14) estimated galactose concentration from the changes in blood reducing substances and glucose concentration.…”
Section: Discussionsupporting
confidence: 76%
“…2A and B, 3A and B). Ulbrich studying human newborns each demonstrated large increases in peripheral glucose concentration and much smaller changes in peripheral galactose concentration after lactose ingestion, similar to the arterial data we report in Figures 2A and 3A. Siddons et al (14) gave lactose to preruminant calves and found quantitatively large increases in peripheral and Glupv with much smaller increases in the peripheral and Galpv. However, Siddons et al (14) estimated galactose concentration from the changes in blood reducing substances and glucose concentration.…”
Section: Discussionsupporting
confidence: 76%
“…Either way, it indicates that ileal disappearance of fructose is lower than that of glucose and glycerol, which could result in osmotic or fermentative diarrhea. Diarrhea has been reported after feeding a fructose solution to milk-fed calves (Velu et al, 1960;Siddons et al, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the delay in 13 CO 2 production after feeding 13 C-labeled fructose compared with glucose and glycerol. Fructose could be converted into glucose (calves; Siddons et al, 1969;Kurz and Willett, 1992), lactate (humans and rats; Pereira and Jangaard, 1971;Swanson et al, 1992;Chong et al, 2007;Teff et al, 2009), and glycogen (rats; Pereira and Jangaard, 1971). In humans, 50% of the fructose, which is metabolized by the liver, is converted into glucose, 25% into lactate, 15 to 18% into glycogen, and 1 to 5% into free fatty acids (as reviewed by Rippe and Angelopoulos, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preceding researchers also observed positive increases in blood reducing sugar with lactose. Maltose, however, did not greatly increase blood reducing sugars in very young calves although the response increased slightly with age (Dollar and Porter, 1957;Huber et al, 1961b;Velu et al, 1960;Siddons et al, 1969) Watson et al (1972) have also demonstrated with cows that feeding ground pelleted maize appreciably increased the quantity of a-linked glucose polymers entering the small intestine. Others (Wright et al, 1966;Karr et al, 1966;Judson et al, 1968;Little et al, 1968;Tucker et al, 1968) Table 4 is a summary of the analysis of variance for total dry matter in duodenal ingesta.…”
Section: Rate Of Flow and Passage Of Digestamentioning
confidence: 96%